Lamb Wave Actuation Techniques for SHM System- A review - Nurazima, Ismail; Mohd Hafizi, Zohari; Lim, Kok-Sing; Harith, Ahmad (Springer, 2022)
Lamb waves-based structural health monitoring (SHM) system has gained significant consideration due to its excellent performance in both precision and versatile accessibility. This paper specifically reviews the active actuation techniques of Lamb waves in the SHM system for diagnostic analysis. It is axiomatic that appropriate signal actuation is of vital necessity and important for a reliable SHM system. Multimodal and dispersive characteristics of the Lamb waves are the main factors for the variety of applied actuation techniques. Multiple Lamb modes synchronously exist, and their dispersive properties are not identical which lead to complex superimposed signals. Various techniques for single mode generation have been proposed to reduce the complexity of the measured signals. Generally, the applied techniques can be clustered to frequency tuning and actuator configuration. The findings showed that the applied techniques were proven to be effective in producing pure mode for further analysis. All these studies have revealed the evolution of Lamb waves-based SHM system for controlling and monitoring the condition of the structure.